Electronically Tunable Quadrature Sinusoidal Oscillator Using VDDDAs - Satipar, Den; Intani, Pattana; Jaikla, Winai (My University, 2021)
This research proposes the sinusoidal oscillator that can provide two sine waves with 90° degree phase shift. The proposed oscillator is derived from lossy and lossless integrator circuits. The proposed quadrature sinusoidal oscillator uses one resistor, two grounded capacitors and two active elements, called voltage differencing differential difference amplifier (VDDDA). By adding additional two resistors, the voltage magnitude of a sinusoidal signal is controllable with low impedance output voltage node. The frequency of the generated sine wave and the condition of oscillation is orthogonally adjusted. In addition, the condition of the signal generator can be adjusted electronically. The performance of the presented sine wave generator has been validated through Pspice simulation. The active element, VDDDA is implemented from two commercial ICs, LM13700 and AD830.
Keywords: Quadrature oscillator; Voltage differencing differential difference amplifier